A general approach to the synthesis and detailed characterization of magnetic ferrite nanocubes. Issue 29 (7th July 2015) - Xu, Yaolin; Sherwood, Jennifer; Qin, Ying; Holler, Robert A.; Bao, Yuping
Abstract : Doped magnetic ferrite nanocubes were synthesized in the presence of sodium oleate in combination with a step-thermal decomposition of metal–oleate complexes. Abstract : A general approach to the synthesis and detailed characterization of magnetic ferrite nanocubes were reported, where the nanocubes were synthesized by the thermal decomposition of metal–oleate complexes following a step-heating method. The doping ions were introduced during the precursor preparation by forming M 2+ /Fe 3+ oleate mixed complex (M 2+ = Fe 2+, Mn 2+, Zn 2+, Cu 2+, Ca 2+, and Mg 2+ ). The mechanistic studies showed that the presence of sodium oleate in combination with step-heating was critical for the formation of the cubic shapes for the doped magnetic ferrites. The nanocubes were extensively characterized, including morphology and crytsal structure by advanced transmission electron microscopy, doping level and distribution by energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy, cation distribution within the spinel structures by Fourier transform infrared and Raman spectroscopy, and magnetic properties by alternating gradient magnetometer at room temperature.